Straßenverkehrsdelinquenz in Deutschland Eine empirische Untersuchung zu Deliktformen, Sanktionierung und Rückfälligkeit - Reiff, Andreas (Universitätsverlag Göttingen, 2015)
Traffic violations represent by far the most significant number of misconducts punished by law. This is due to the fact that the majority of the population actively participates in road traffic. Despite the importance of this topic, only a limited number of empirical studies have been conducted about traffic offenses. The present study intends to reduce this deficit in the field of traffic infringements by analyzing nationwide data about sentences and cases of repeated offenses, differentiating by seriousness of the misdemeanors and their general and traffic specific penalties. For the first time, a complete data set from the "Bundeszentralregister" (Federal Central Criminal Register) is evaluated. This traffic violation data set contains records of 250,000 people. As a result, this research incorporates nearly all people convicted in a specific year in Germany. Under due consideration of criminal records, these data are classified into distinct categories depending on the seriousness of the offense and the type of punishment. Furthermore, this study appraises the correlation between traffic specific reconviction rates and the success of related punishments.